Analisis Aspek Kepribadian Tokoh Qays dalam Novel LAYLA MAJNUN Karya Syekh Nizami - Siva Milano Salima; Agirl Khayatul Iman; Eva Dwi Kurniawan (Lembaga Pengembangan Kinerja Dosen, 2024)
Layla's Majnun by Sheikh Nizami was one of the classics. This book is interesting because it describes the poignant and tragic love story between qays and layla. The study aims to quantify the results of the main character's personality analysis (qays) in literature. The problem that was raised was how qays was in layla majnun's novel. The methods used approach literary psychology. Results have shown that the novel contains a number of relevant psychological aspects to analyze on male figures (qays), such as id, ego, superego, and erotomania.